Raja Marga Yoga Teachings as the Javanese View of Life in the Sêrat Bhagawad Gita - Hartanto, Doni Dwi; Nurhayati, Endang (Jurnal Penelitian Agama Hindu, 2025)
The view of life is believed by a group of society as the guideline in living life to reach the true purpose of life. This study is aimed at explaining the view of the life of Javanese society following Raja Marga Yoga teachings as the path to reaching their God in Sêrat Bhagawad Gita. The data sources are text Piwulang Panunggal sarana Kawruh kang Luhur, tuwin Wêwados Kang Luhur in the manuscript of Sêrat Bhagawad Gita. It employed a qualitative research method to interpret the view of life in the texts. Data collection was conducted using reading-note techniques with the researcher as the main instrument. The validity of the data used was semantic validity and inter-intrarater reliability. Data analysis was conducted using qualitative model analysis. The result of this study revealed that Raja Yoga is the way to reach God by implementing the highest yoga technique, a secret knowledge. The harmony of the Javanese way of life of Raja Marga Yoga is as follows: 1) the greatness of dharma; 2) God is the source of all sentient beings; 3) praising the God: a) Mardikå sarånå Seleh Pandamêl, b) Mardikå sarånå Bêkti. By implementing Raja Marga Yoga, the human being will be able to achieve the true objectives of life which are being united with God.